Evaluation After Sudden Death in the Young: A Global Approach. (August 2019) - Gray, Belinda; Ackerman, Michael J.; Semsarian, Christopher; Behr, Elijah R.
Abstract : Sudden cardiac death is defined as a death occurring usually within an hour of onset of symptoms, arising from an underlying cardiac disease. Sudden cardiac death is a complication of a number of cardiovascular diseases and is often unexpected. In individuals aged <35 years, unexplained sudden cardiac death is the most common presentation. A significant proportion of sudden cardiac death in the young (⩽35 years) events may be precipitated by underlying inherited cardiac conditions, including both heritable cardiomyopathies and inherited arrhythmia syndromes (also known as cardiac channelopathies). Tragically, sudden death may be the first manifestation of the disease in a family and, therefore, clinical and genetic evaluation of surviving family members forms a key role in diagnosing the underlying inherited cardiac condition in the family. This is particularly relevant when considering that most inherited cardiac conditions are inherited in an autosomal dominant manner meaning that surviving family members have a 50% chance of inheriting the same disease substrate. This review will outline the underlying causes of sudden cardiac death in the young and outline our universal approach to familial evaluation following a young person's sudden death.